Psychological well-being pada penyintas COVID-19: Menguji peranan kebersyukuran - Fitriana, Lutvia Fitriana; Herlan Pratikto; Akta Ririn Aristawati (INNER: Journal of Psychological Research, 2023)
Abstract COVID-19 survivors have a fear of societal stigma and feel themselves excluded by the social environment, causing the impact of unhappiness and psychological well-being on COVID-19 survivors. The way to look positively is to be grateful, because being grateful to provide benefits to individuals facing problems that have an impact on psychological well-being in COVID-19 survivors. The research design uses quantitative methods with product moment analysis techniques. The study was conducted on 102 COVID-19 survivors in the work area of puskesmas Mojo Surabaya using the purposive sampling method. The study was measured using the psychological well-being scale by Ryff and the diversity scale by Fitzgerald (in Listiyandini, 2015). The results showed a correlation coefficient of 0.655 with a significance of 0.000. It was concluded that psychological well-being and psychological well-being have a positive and significant relationship between the variables of fitness and psychological well-being in COVID-19 survivors. Researchers can then link psychological well-being with other variables, so that research on psychological well-being is more diverse. Abstrak Penyintas COVID-19 memiliki rasa takut akan stigma masyarakat dan merasa dirinya dikucilkan oleh lingkungan sosial, menyebabkan dampak ketidakbahagiaan dan psychological well-being pada diri penyintas COVID-19. Cara untuk memandang positif yaitu dengan bersyukur, karena bersyukur memberikan manfaat pada individu menghadapi permasalahan yang berdampak pada psychological well-being pada penyintas COVID-19. Tujuan penelitian ini melihat hubungan kebersyukuran dan psychological well-being pada penyintas COVID-19. Rancangan penelitian menggunakan metode kuantitatif dengan teknik analisis product moment. Penelitian dilakukan kepada 102 penyintas COVID-19 di wilayah kerja Puskesmas Mojo Surabaya dengan menggunakan metode purposive sampling. Penelitian diukur menggunakan skala psychological well-being oleh Ryff dan skala kebersyukuran oleh Fitzgerald (dalam Listiyandini, 2015). Hasil penelitian menunjukkan koefisien korelasi sebesar 0,655 dengan signifikansi 0,000. Disimpulkan kebersyukuran dan psychological well-being memiliki hubungan positif dan signifikan antara variabel kebersyukuran dan psychological well-being pada penyintas COVID-19. Peneliti selanjutnya dapat menghubungkan psychological well-being dengan variabel lain, agar penelitian mengenai psychological well-being lebih beragam. Kata kunci: Psychological well-being, Kebersyukuran, Penyintas COVID-19.